2014
DOI: 10.1038/gt.2014.62
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-based short hairpin RNA against connective tissue growth factor attenuated monocrotaline-induced pulmonary vascular remodeling in rats

Abstract: Pulmonary hypertension is a life-threatening medical condition, and a growing body of evidence shows that the expression of connective tissue growth factor (CTGF) is significantly associated with its pathogenesis, making it an attractive therapeutic target. Our earlier work revealed that plasmid-based CTGF-specific short hairpin RNA (shRNA) could attenuate pulmonary artery smooth muscle cell (PASMC) proliferation and pulmonary vascular remodeling in rats exposed to cigarette smoke. In this study, we explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…In our previous studies, we showed that intratracheal administration of CTGF or CCND1 shRNA could significantly, but only partially, restore monocrotaline-induced pulmonary artery remodeling [28, 29]. In the present study, we found that downregulation of miR-26b was responsible for the upregulation of CTGF and CCND1 in monocrotaline-induced pulmonary artery remodeling, and intratracheal administration of miR-26b could almost completely restore the pulmonary artery remodeling in monocrotaline-treated rats.…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations
“…In our previous studies, we showed that intratracheal administration of CTGF or CCND1 shRNA could significantly, but only partially, restore monocrotaline-induced pulmonary artery remodeling [28, 29]. In the present study, we found that downregulation of miR-26b was responsible for the upregulation of CTGF and CCND1 in monocrotaline-induced pulmonary artery remodeling, and intratracheal administration of miR-26b could almost completely restore the pulmonary artery remodeling in monocrotaline-treated rats.…”
Section: Introductionsupporting
confidence: 53%
“…The expression patterns were analyzed and compared between the two groups, and no pattern was identified specific to monocrotaline treatment. Furthermore, the most significantly down-regulated miRNAs, miR-26b, was selected for further functional analysis due to its well documented role in regulating human cell proliferation [30, 31], as well as the predicted function to suppress the expression of CTGF and CCND1(www.targetscan.org), upregulation of which have both been reported to contribute to the development of PAH in our previous studies [29, 32, 33]. The following confirmatory real-time PCR showed mRNA expression levels of rPASMCs isolated from monocrotaline-treated rats and the controls for selected miRNA (Figure 2A, *P<0.01), and a comparable change were identified compared with our precedent microarray experiment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While little is known regarding LXR’s in PH, macrophage specific LXR signaling is important in inhibiting macrophage activation and is anti-fibrotic via inhibition of macrophage recruitment and macrophage-induced IL6 release (3033). While hypoxic mice demonstrate only mild pulmonary vascular remodeling, we found that connective tissue grown factor (CTGF), a well-established mediator of pulmonary vascular remodeling in PH, was activated in day 14 IM’s relative to day 4 IM’s (34, 35). We hypothesize that the coordinated “anti-inflammatory” and “pro-reparative” programming state in IM’s in hypoxic mice limits progressive perivascular remodeling seen in other animal models of PH.…”
Section: Discussionmentioning
confidence: 90%